Palliative care: definition and strategies used in medical practive (Research, Society and Development, 2021)
The term care encompasses different practices and meanings, varying according to the culture to which it belongs. Palliative care presents itself as a sphere of care, which emerged with the objective of meeting a growing demand from patients outside the possibilities of therapeutic cure and who were being marginalized and poorly assisted by the technical model of Medicine, focusing on the disease in to the detriment of the patient. The purpose of this article is to define palliative care from the perspective of doctors who work in an oncology unit in a large hospital and the strategies used to operationalize this type of health care. This is a qualitative, descriptive study, carried out with 14 doctors working in an oncology unit of a hospital in the Midwest region of Minas Gerais, following inclusion and exclusion criteria, and later divided into three categories of analysis: definition of palliative care; the weakness of medical training in palliative care; multidisciplinarity and the operationalization of care. This study points out that knowledge in palliative care is still weak and superficial, demonstrating a gap in medical teaching when we take this theme as a reference. Thus, professional training strategies are necessary for this type of care to provide assistance to the individual following the principle of integrality. In order to be effective, the operationalization of this biopsychosocial and spiritual care requires dialogue through interdisciplinary work, constituting the Singular Therapeutic Plan (PTS) as a promising tool.